EDUCATIONAL VIDEO FOR SELF-CARE OF PATIENTS WITH INTESTINAL ELIMINATION STOMA - Moreira, Bruna Camila Blans; Lima, Fernando Conceição de; Silva, Cassilene Oliveira da; Carvalho, Dione Seabra de; Simor, Alzinei; Santana, Mary Elizabeth de; Nascimento, Marcia Helena Machado (Cogitare Enfermagem, 2023)
Objective: to describe the construction of an educational technology to mediate the self-care of cancer patients with intestinal elimination stoma. Method: methodological research, conducted in two stages - situational diagnosis and integrative literature review, carried out in the oncology reference hospital in the city of Belém-Pará, Brazil. The collection was carried out in the period from January to November 2021, through semi-structured interviews, with 10 oncology patients with stomas and in electronic databases. They were analyzed from the perspective of content analysis of the thematic type and supported by the Iramuteq software. Results: from the corpus a tree of similarity emerged, in which the word "Bag" has greater centrality and strong connection with the words, "Care", "Change", "Plaque", "Colostomy" and "Stoma". Based on this context, an educational video technology was produced. Conclusion: the production of context-based technology favors the collection of social evidence for self-care with the peristomal skin.